Interlaminar stabilization and decompression for the treatment of bilateral juxtafacet cysts: Case report and literature review. (2019) - Cajigas, Iahn; Varon, Alberto; Levene, Howard B.
Highlights: Lumbar juxtafacet cysts are typically treated by resection alone or resection combined with posterior instrumentation. Resection with instrumentation is associated with a lower rate of recurrence but also with increased cost and morbidity. We present a case of bilateral juxtafacet cysts causing neurogenic claudication treated with decompression and interlaminar stabilization. Complete symptom resolution was sustained at one-year follow-up. Decompression followed by interlaminar stabilization may be a reasonable alternative for some patients. Abstract: Introduction: Lumbar juxtafacet cysts (JFCs) are a common cause of lumbar radiculopathy which tend to occur in areas of increased facet mobility. While resection alone is a possible treatment, recent publications suggest that laminectomy alone for JFCs may not yield as favorable an outcome as laminotomies reinforced with posterior dynamic hardware. The Coflex ® is a novel interlaminar stabilization device that has been shown to achieve comparable results to rigid fusion in the management of lumbar stenosis in patients with no more than grade one anterolisthesis, and superior performance compared to laminectomy alone when a combined outcome score was used. We describe the combined use of dynamic posterior element fusion with primary cyst resection in the management of bilateral JFCs. Presentation of case: A 71-year-old man who developed a progressive left L4 radiculopathy along with new urinary incontinence was found to have bilateral L3/4 JFCs causing significant lumbar stenosis and neurogenic claudication. After treatment with primary cyst resection and interlaminar stabilization, the patient experienced complete symptom resolution and was discharged to inpatient-rehabilitation on post-operative day 1. Discussion: While current recommendations for the management of juxtafacet cysts causing progressive neurologic symptoms include surgical cyst removal and lumbar decompression with or without fusion, the role of dynamic interlaminar stabilization has not been explored. Conclusion: Direct decompression followed by interlaminar stabilization may represent an alternative for patients to simultaneously benefit from a decompression of their juxtafacet cysts while affording posterior element reconstruction.